Rare Branching Pattern of the Subscapular Artery - Tverskoi, Alexey Vladimirovich; Morozov, Vitaly Nikolaevich; Petrichko, Svetlana Aleksandrovna; Pushkarskiy, Vitaly Vladimirovich; Parichuk, Aleksandr Sergeevich (Journal of Morphological Sciences, 2018)
Variations of the axillary artery and its branches are quite common. Some variations are clinically significant and having knowledge of them can be useful for the prevention of diagnostic errors during surgical interventions in the axillary fossa. Classically, the third part of the axillary artery presents three branches—the subscapular, the anterior, and the posterior circumflex humeral arteries. The subscapular artery is divided into the circumflex scapular and the thoracodorsal arteries. Our work presents a previously undescribed branching pattern of the right subscapular artery. It branched into the thoracodorsal, the circumflex scapular, the profunda brachii, and the anterior and posterior circumflex humeral arteries. The profunda brachii artery was 0.4 cm in diameter and ran inferiorly to the humeromuscular canal. No branches of the profunda brachii artery were found in the superior part of the arm before entering the humeromuscular canal. No variations in the other parts of the right axillary artery and of the left axillary artery were discovered. The described branching pattern of the subscapular artery can be important and essential for surgeons and radiologists.
Keywords: artery; axillary; subscapular; variation